Performance of Kedah-Kelantan Cattle Fed Palm Kernel Cake - Mak, T. K.; Hutagalung, R. I.; Togimin, Tokiran (1986)
An experiment involving a completely randomized design was conducted to compare the effect of PKC-S-B and PKC-S-F on the performance of Kedah-KeLantan bulls. No significant difference exists between the PKC-S-B and PKC-S-F treatment groups. Kedah-Kelantan bulls when fed an average daily feed of 3. 824 kg PKC-S for a period of 175 days could achieve an average daily gain of 0.583 kg. The feed efficiency obtained was 6.559. The income over feed cost l head/day obtained was M$1.096.